2014
DOI: 10.1002/mas.21439
|View full text |Cite
|
Sign up to set email alerts
|

Advanced mass spectrometry‐based multi‐omics technologies for exploring the pathogenesis of hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is one of the primary hepatic malignancies and is the third most common cause of cancer related death worldwide. Although a wealth of knowledge has been gained concerning the initiation and progression of HCC over the last half century, efforts to improve our understanding of its pathogenesis at a molecular level are still greatly needed, to enable clinicians to enhance the standards of the current diagnosis and treatment of HCC. In the post‐genome era, advanced mass spectrometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 78 publications
(118 reference statements)
0
24
0
1
Order By: Relevance
“…In the postgenomics era, system-wide overview provided by multi-omics studies contributes valuable insights on algal research in biofuels development (Rai et al, 2016), veterinary medicine (Li et al, 2015), and systemic progression on pathogenesis in liver cancer research (Nie et al, 2016), respectively. Proteomics, as an important technique in multi-omics study, still has limitations, despite improvements that were made in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…In the postgenomics era, system-wide overview provided by multi-omics studies contributes valuable insights on algal research in biofuels development (Rai et al, 2016), veterinary medicine (Li et al, 2015), and systemic progression on pathogenesis in liver cancer research (Nie et al, 2016), respectively. Proteomics, as an important technique in multi-omics study, still has limitations, despite improvements that were made in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…With the trend of increasing use of mass spectrometry in clinical care, MS based biomarkers are being validated for future incorporation into diagnostic criteria. Mass spectrometry has been used to study biomarker panels found in various cancers, [ 86–92 ] cystic fibrosis, [ 93 ] neurodegenerative diseases, [ 94,95 ] major depressive disorder, [ 96 ] nephrotic syndromes, [ 97 ] myocardial injury, [ 98 ] and even Fabry disease. [ 99 ] Some researchers provide a further push for this concept by coming up with innovative ways of using mass spectrometry data in clinical care.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The protein numbers identified per sample was slightly higher than those obtained from human kidney tissues 17 . 9 To evaluate the quantitative accuracy of the method, we computed the global Pearson correlation of the two technical replicates at the peptide level for all samples after removing missing values. The R 2 was 0.9729 ( Fig.…”
Section: Identification Of Peptides and Proteins By Pct-swathmentioning
confidence: 99%
“…Better biomarkers are needed for HCC. The search for HCC biomarkers from clinical specimens using proteomics approaches has been focused mainly on blood samples 9,10 . Besides, some studies also investigated biological fluids including urine 11 and tissue interstitial fluid 12 .…”
Section: Introductionmentioning
confidence: 99%